An Oral Microencapsulated Vaccine Loaded by Sodium Alginate Effectively Enhances Protection Against GCRV Infection in Grass Carp (Ctenopharyngodon idella) - Xu, Chuang; Qiao, Meihua; Huo, Xingchen; Liao, Zhiwei; Su, Jianguo (Frontiers in Immunology, 2022)
Grass carp reovirus (GCRV) is highly infectious and lethal to grass carp, causing huge economic losses to the aquaculture industry annually. Currently, vaccination is the most effective method against viral infections. Among the various vaccination methods, the oral vaccination is an ideal way in aquaculture. However, low protective efficiency is the major problem for oral vaccination owing to some reasons, such as antigen degradation and low immunogenicity. In our study, we screened the antigenic epitopes of GCRV-II and prepared an oral microencapsulated vaccine using sodium alginate (SA) as a carrier and flagellin B (FlaB) as an adjuvant, and evaluated its protective effects against GCRV-II infection in grass carp. The full length and three potential antigenic epitope regions of GCRV-II VP56 gene were expressed in Escherichia coli and purified by glutathione affinity column respectively. The optimal antigen (VP56-3) was screened by enzyme-linked immunosorbent assay (ELISA). Adjuvant FlaB was also expressed in E. coli and purified by Ni2+ affinity column. Subsequently, we prepared the oral vaccines using sodium alginate as a carrier. The vaccine (SA-VP56-3/FlaB) forms microsphere (1.24 ± 0.22 μm), examined by transmission electron microscopy, scanning electron microscopy, and dynamic light scattering assay. SA-VP56-3/FlaB vaccine has excellent stability, slow-release, and low toxicity by dynamic light scattering assay, release dynamic assay, in vivo fluorescence imaging system, hemolytic activity and cytotoxicity. Then we vaccinated grass carp orally with SA-VP56-3/FlaB and measured immune-related parameters (serum neutralizing antibody titer, serum enzyme activity (TSOD, LZM, C3), immune-related genes ((IgM, IFN1, MHC-II, CD8 in head kidney and spleen), IgZ in hindgut)). The results showed that SA-VP56-3/FlaB significantly induced strong immune responses, compared to other groups. The highest survival rate achieved in SA-VP56-3/FlaB microencapsulated vaccine (56%) in 2 weeks post GCRV challenge, while 10% for the control group. Meanwhile, the tissue virus load in survival grass carp is lowest in SA-VP56-3/FlaB group. These results indicated that SA-VP56-3/FlaB could be a candidate oral vaccine against GCRV-II infection in aquaculture.